MAKING CHEMINOSMART MEDIA ON INORGANIC COMPOUND NOMENCLATURE MATERIAL - Gina Lestari; Ida Farida; Imelda Helsy (Gunung Djati Conference Series, 2021)
Chemistry subject is an abstract and theoritical material. One of them is in the nomenclature of inorganic compounds. Student will find it difficult to understand the material if the learning process uses inappropriate learning media. Thus, it can reduce student attractiveness and interest in learning. The use of cheminosmart media can help students understand the nomenclature of inorganic compounds. Students will collaborate and be fully involved in a cheminosmart game match. The purpose of this study was to describe the appearance of the product and to analyze the results of the cheminosmart media validation test on the nomenclature of inorganic compounds. The research method used was Design Based Research (DBR) using flowchart instruments, story boards and validation questionnaires. The results of the validation test showed that the average value of rcount was 0.87, so that the cheminosmart game media is declaired valid and can be used as an effective learning media.